Alterations in protein phosphorylation in the amygdala of the 5XFamilial Alzheimer's disease animal model - Eun-Jeong Yang; Usman Mahmood; Hyunju Kim; Moonseok Choi; Yunjung Choi; Jean-Pyo Lee; Moon-Jeong Chang; Hye-Sun Kim (Elsevier, 2017)
Alzheimer's disease is the most common disease underlying dementia in humans. Two major neuropathological hallmarks of AD are neuritic plaques primarily composed of amyloid beta peptide and neurofibrillary tangles primarily composed of hyperphosphorylated tau. In addition to impaired memory function, AD patients often display neuropsychiatric symptoms and abnormal emotional states such as confusion, delusion, manic/depressive episodes and altered fear status. Brains from AD patients show atrophy of the amygdala which is involved in fear expression and emotional processing as well as hippocampal atrophy. However, which molecular changes are responsible for the altered emotional states observed in AD remains to be elucidated. Here, we observed that the fear response as assessed by evaluating fear memory via a cued fear conditioning test was impaired in 5XFamilial AD (5XFAD) mice, an animal model of AD. Compared to wild-type mice, 5XFAD mice showed changes in the phosphorylation of twelve proteins in the amygdala. Thus, our study provides twelve potential protein targets in the amygdala that may be responsible for the impairment in fear memory in AD.